Now and Forward: Customer Deposit Insurance of Sharia Bank in Indonesia - Nun Harrieti; Azlin Alisa Ahmad; Eidy Sandra; Fatmi Utarie (Udayana Journal of Law and Culture, 2023)
Sharia banking's characteristic, which underpins its activities on sharia principles, requires a customer protection mechanism in accordance with its characteristics, including customer deposit insurance. This study aims to determine the readiness of sharia banking regulations on customer deposit insurance in Indonesia to strengthen the protection mechanism for Sharia Banking Customers. This article is a normative juridical research that applies an analytical descriptive approach. The insurance for customer deposits of sharia bank in Indonesia is regulated explicitly in the Regulation of Deposit Insurance Cooperation No. 1 of 2020 concerning the Implementation of Sharia Bank Deposit Insurance and Resolution. The regulation determines that deposit insurance must be carried out through a kafalah contract between the Deposit Insurance Corporation and the Customer. However, it does not yet provide a specific arrangement regarding the protection of deposits on social funds in sharia banking. In the future, it is necessary to have regulations related to deposit insurance for social funds in sharia banking in implementing the social functions of sharia banking, especially as Sharia Financial Institutions-Recipients of Money Waqf and arrangement of Money Waqf Nazhir.